“Happy Life”: Digital Ageism and Beauty Filter Use Among Older Content Creators on Douyin - Wang, Yingwen; Sujon, Zoetanya (AoIR Selected Papers of Internet Research, 2026)
The proliferation of beauty filters on digital platforms has transformed self-presentation practices, yet their prevalence and impact on older users remains underexplored. This study investigates why older content creators on Douyin engage with beauty filters, interrogating the emotional, social, and structural dynamics of digital ageism. Through in-depth interviews with twelve creators and participant observation of two individuals, the research reveals how older adults use filters to navigate algorithmic constraints, societal stigma, and self-perception. This research brings together work on visibility with aging and digital cultures to understand the role of filters in older content creator’s practices. Findings demonstrate that filters serve as tools for social recognition as well as emotional well-being and resistance against ageist invisibility, simultaneously reinforce youth-centric norms. By situating filter use within frameworks of digital ageism, this study highlights the paradox of digital visibility: older content creators balance authenticity with enhancement to negotiate their place in a youth-dominated ecosystem. The results advocate for inclusive design and algorithmic accountability to challenge systemic and aesthetic ageism in digital cultures.